A Simple Environment-Based Chemistry Lab Guide for High School Students - Hardeli Hardeli; Fajriah Fajriah; Suryelita Suryelita; Bayharti Bayharti; Yeri Mardesi; Andromeda Andromeda (Fakultas MIPA Universitas Negeri Padang, 2021)
This research is to create a practical guide alternative based environment forsenior high school students and determine the validity, practicality, and effectivity level of the practical guide itself. The type of this research is Research and Development (R & D). The development model used in this research is the Plomp model which consists of three phases: preliminary research, prototyping phase, and assessment phase. The research instrumentis questionnaire of validity, practicality, and effectivity sheet. Practical guide alternative-based environment validated by 4 validators and tested to 17 students of class XII IPA 3 SMAN 1 Rambatan and 29 students of class XI IPA 4 SMA N 1 Kec. Guguak of the academic year 2017/2018. The moment kappa of validity was 0.79. The practicality level of the teacher's response questionnaire was 0.84. Based on the questionnaire of student response, the value of moment kappa is 0,77 in SMAN 1 Rambatanand and 0,90 in SMAN 1 Kec.Guguak with high category practicality for small group test and moment kappa value is 0,81 in SMAN 1 Rambatan and 0,84 in SMAN 1 Kec. guguak with the highest category practicality on the field test. The effectivity level of the teacher's response questionnaire was 0,89. Based on the questionnaire of student response, the value of momen kappa is 0,76. The results of the research can be concluded that the practical guide alternative based environmentfor senior high school students has a high validity category, highest practicality category, high effectivity category from students, and highest effectivity from teachers.